Whole grain and cereal fibre intake in the Australian Health Survey: associations to CVD risk factors. Issue 8 (23rd June 2020) - Barrett, Eden M; Batterham, Marijka J; Beck, Eleanor J
Abstract: Objective: To explore associations of whole grain and cereal fibre intake to CVD risk factors in Australian adults. Design: Cross-sectional analysis. Intakes of whole grain and cereal fibre were examined in association to BMI, waist circumference (WC), blood pressure (BP), serum lipid concentrations, C-reactive protein, systolic BP, fasting glucose and HbA1c. Setting: Australian Health Survey 2011–2013. Participants: A population-representative sample of 7665 participants over 18 years old. Results: Highest whole grain consumers (T3) had lower BMI (T0 26·8 kg/m 2, T3 26·0 kg/m 2, P < 0·0001) and WC (T0 92·2 cm, T3 90·0 cm, P = 0·0005) compared with non-consumers (T0), although only WC remained significant after adjusting for dietary and lifestyle factors, including cereal fibre intake ( P = 0·03). Whole grain intake was marginally inversely associated with fasting glucose ( P = 0·048) and HbA1c ( P = 0·03) after adjusting for dietary and lifestyle factors, including cereal fibre intake. Cereal fibre intake was inversely associated with BMI ( P < 0·0001) and WC ( P < 0·0008) and tended to be inversely associated with total cholesterol, LDL-cholesterol and apo-B concentrations, although associations were attenuated after further adjusting for BMI and lipid-lowering medication use. Conclusions: The extent to which cereal fibre is responsible for the CVD-protective associations of whole grains may vary depending on the mediators involved. Longer-term intervention studies directly comparing whole grain and non-whole grain diets of similar cereal fibre contents (such as through the use of bran or added-fibre refined grain products) are needed to confirm independent effects.